Methodological aspects of a questionnaire researching transportation links - Litvinenko, Michail; Palšaitis, Ramūnas (Transport, 2005)
Changes of foreign trade conditions also bring changes of the main transport routes and directions. Lithuanian transport companies must perfect their ability to adapt in changing environment, to predict and reorient to the possible changes in the flow of goods, to observe changes and tendencies, in short to build a new foundation and appliance of transportation technologies. To aid this a questionnaire researching transport must be made. This article covers the analysis of the planning and conducting of the research and the data processing methodology used to determine the main directions of the flow of goods of Lithuanian transport companies as well as the criteria concerning competitiveness among the companies. First Published Online: 27 Oct 2010